2023
DOI: 10.1101/2023.01.09.23284358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential COVID-19 mortality in the United States: Patterns, causes and policy implications

Abstract: A "two Americas" narrative emerged in the summer of 2021: one with high demand for COVID-19 vaccines, and a second with widespread vaccine hesitancy and opposition to mask mandates.  But our analysis of excess mortality shows that the U.S. has been a divided nation at least since the start of the pandemic.  Through April, 2022, there were 1,335,292 excess deaths associated with COVID-19, 37% more than reported as such.  After the first wave, death rates in the South were more than double those in the Northeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Two of the ecological studies compared mortality between states or countries and suggested reasons explaining high mortality settings without investigating these further. 21 74 We identified no analytical studies that investigated the importance of influenza or other infections, prevalence of chronic conditions, wider societal issues or displacement as hypotheses for continuing high mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the ecological studies compared mortality between states or countries and suggested reasons explaining high mortality settings without investigating these further. 21 74 We identified no analytical studies that investigated the importance of influenza or other infections, prevalence of chronic conditions, wider societal issues or displacement as hypotheses for continuing high mortality.…”
Section: Resultsmentioning
confidence: 99%